Pathogen genomics and phage-based solutions for accurately identifying and controlling Salmonella pathogens - Lopez-Garcia, Angela V.; AbuOun, Manal; Nunez-Garcia, Javier; Nale, Janet Y.; Gaylov, Edouard E.; Phothaworn, Preeda; Sukjoi, Chutikarn; Thiennimitr, Parameth; Malik, Danish J.; Korbsrisate, Sunee; Clokie, Martha R. J.; Anjum, Muna F. (Frontiers in Microbiology, 2023)
Salmonella is a food-borne pathogen often linked to poultry sources, causing gastrointestinal infections in humans, with the numbers of multidrug resistant (MDR) isolates increasing globally. To gain insight into the genomic diversity of common serovars and their potential contribution to disease, we characterized antimicrobial resistance genes, and virulence factors encoded in 88 UK and 55 Thai isolates from poultry; the presence of virulence genes was detected through an extensive virulence determinants database compiled in this study. Long-read sequencing of three MDR isolates, each from a different serovar, was used to explore the links between virulence and resistance. To augment current control methods, we determined the sensitivity of isolates to 22 previously characterized Salmonella bacteriophages. Of the 17 serovars included, Salmonella Typhimurium and its monophasic variants were the most common, followed by S. Enteritidis, S. Mbandaka, and S. Virchow. Phylogenetic analysis of Typhumurium and monophasic variants showed poultry isolates were generally distinct from pigs. Resistance to sulfamethoxazole and ciprofloxacin was highest in isolates from the UK and Thailand, respectively, with 14–15% of all isolates being MDR. We noted that >90% of MDR isolates were likely to carry virulence genes as diverse as the srjF, lpfD, fhuA, and stc operons. Long-read sequencing revealed the presence of global epidemic MDR clones in our dataset, indicating they are possibly widespread in poultry. The clones included MDR ST198 S. Kentucky, harboring a Salmonella Genomic Island-1 (SGI)-K, European ST34 S. 1,4,[5],12:i:-, harboring SGI-4 and mercury-resistance genes, and a S. 1,4,12:i:- isolate from the Spanish clone harboring an MDR-plasmid. Testing of all isolates against a panel of bacteriophages showed variable sensitivity to phages, with STW-77 found to be the most effective. STW-77 lysed 37.76% of the isolates, including serovars important for human clinical infections: S. Enteritidis (80.95%), S. Typhimurium (66.67%), S. 1,4,[5],12:i:- (83.3%), and S. 1,4,12: i:- (71.43%). Therefore, our study revealed that combining genomics and phage sensitivity assays is promising for accurately identifying and providing biocontrols for Salmonella to prevent its dissemination in poultry flocks and through the food chain to cause infections in humans.